Food Structure and Moisture Transfer A Modeling Approach - Guillard, Valérie; Bourlieu, Claire; Gontard, Nathalie; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
It's well known that the structural characteristics of food materials influence their mass transfer, especially their water transfer properties during such processes as drying, hydration, and storage. In porous cereal-based products, for example, effective water diffusivity is highly affected by the volume fraction and distribution of both solid and gas phases, while in dense food materials, such as fat-based or other edible coatings, it depends on factors that affect the "tightness" of the molecular structure (e.g., free volume, cohesive energy density, crystallinity). This Brief will review the impact of food structure on moisture transfer. A multi-scale analysis of food structure will include a look at molecular structure (e.g., free volume, crystallinity), nanostructure, microstructure (e.g., porous food), and macrostructure (e.g., bilayer structure). For each structural analysis, a focus on the mathematical modelling of the relationship between structural properties and moisture transfer properties will be performed.
Theoretical Background.- Relationship Between Multi-scale Food Structure and Moisture Transfer Properties -- Integration of the Various Scales: Examples of Hydrophobic Dense Edible Coatings -- Concluding Remarks -- References.
Keywords: Food—Biotechnology.; Biochemical engineering; Nanochemistry; Food Science; Biochemical Engineering; Nanochemistry